Assessing the economic value of a seagrass ecosystem in Southern Cebu, Philippines - JAN AXEL B. INOCENTES; KHERSTINE D. ESCALANTE; ANGELINE I. GINOO; GODWIN T. PRADO; GRACIELA MAE L. UY; ARABELLE E. JUSTOL; JANEYLYN L. FERNANDEZ; JELYN O. GACANG; CATHERINE D. LACORTE; SYLVESTER T. CORTES; ZERRY AYN Z. RETUBADO; ANNE S. LORCA; JOSEPH JOEL N. ALMAGRO (Society for Indonesian Biodiversity, 2025)
Abstract. Inocentes JAB, Escalante KD, Ginoo AI, Prado GT, Uy GML, Justol AE, Fernandez JL, Gacang JO, Lacorte CD, Cortes ST, Retubado ZAZ, Lorca AS, Almagro JJN. 2025. Assessing the economic value of a seagrass ecosystem in Southern Cebu, Philippines. Biodiversitas 26: 1898-1912. Seagrass meadows are critical habitats that support marine biodiversity, enhance coastal protection, and serve as nurseries for various fish species, which are the foundation for local fisheries and tourism. By assigning a monetary value to these resources, we can better implement conservation efforts that safeguard and ensure their sustainability. In this regard, this study investigates the economic valuation of the seagrass ecosystem in Argao, Cebu, Philippines, a coastal municipality rich in marine biodiversity and dependent on fishing and ecotourism. We employ a mixed-methods approach, integrating surveys, interviews, and observations to collect data from stakeholders, including fishers, tourists, and local officials from ten coastal barangays. The economic assessment employs the Total Economic Value (TEV) framework, encompassing direct uses like fisheries and tourism, indirect benefits such as coastal protection and carbon sequestration, and non-use values, including bequest and existence values. Through a comprehensive assessment of the ecosystem services provided by seagrass beds, the findings highlight the critical role of Marine Protected Areas (MPAs) in Argao, which include ten key areas essential for marine life. The study reveals that the total economic value of the seagrass ecosystem is ?56,299,100.61 (USD 960,080.16). The findings aim to offer a holistic understanding of the seagrass ecosystem's contribution to local livelihoods and global ecological services, thereby informing sustainable management and conservation strategies. The study also identifies key challenges, such as temporal data limitations and complexities in estimating non-market values, but it also underscores the potential for further research to address both ecological and social dimensions fully, offering hope for the future.